Managing Gas Price Policy Communication at Perusahaan Gas Negara Tbk - Adil Wahyudin Anwar; La Mani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
This study examined how PT Perusahaan Gas Negara (Persero) Tbk managed the communication of gas price increases to industrial and commercial customers in Bogor Area. As declining pipeline gas was increasingly balanced by Liquefied Natural Gas supply, price adjustment required more careful policy communication. A convergent mixed-methods case study was used. Qualitative data came from interviews with the General Manager, Area Head, and Customer Management officers, while quantitative data came from questionnaires completed by 81 customers. The findings showed that PGN’s communication was educational, situational, and relational. Email supported formal notification, WhatsApp and telephone accelerated clarification, and direct visits were most important for trust building. Customers rated the process positively, but the logical acceptance of the price increase remained the weakest aspect.